THE ROLE OF SLEEP QUALITY IN CARDIOMETABOLIC HEALTH: MECHANISMS AND CLINICAL EVIDENCE – A NARRATIVE REVIEW - Aleksandra Iwona Włodarczyk; Norbert Grabias; Jędrzej Piotrowski; Paulina Jarząbek; Maria Rajkowska; Julia Weronika Mieszkowska; Radosław Gryko; Bernard Myszewski; Anna Kinga Tejchma; Łukasz Dominik Woźniak (International Journal of Innovative Technologies in Social Science, 2026)
Background: Sleep quality is increasingly recognized as a fundamental pillar of health, recently emphasized in the American Heart Association’s “Life’s Essential 8”. However, the multidimensional pathways linking sleep-such as duration, continuity, and regularity to metabolic and cardiovascular function remain complex. Objective: This narrative review synthesizes clinical evidence and biological mechanisms connecting multidimensional sleep health with cardiometabolic outcomes, including metabolic syndrome, type 2 diabetes, coronary heart disease, and the newly defined Cardiovascular-Kidney-Metabolic (CKM) syndrome. Methods: Peer-reviewed publications from 2018-2025 were analyzed, including prospective cohort studies, randomized controlled trials, meta-analyses, and scientific statements. Mechanisms involving inflammation, autonomic regulation, neuroendocrine activity, epigenetic modifications, and gut microbiota were evaluated. Results: Poor sleep quality and irregular sleep patterns consistently correlate with increased metabolic dysregulation, obesity, and Major Adverse Cardiovascular Events (MACE). Recent findings link inadequate sleep with advanced CKM stages and accelerated epigenetic aging. Interventional studies show that extending sleep duration can reduce energy intake and support weight loss, although improvements in insulin sensitivity remain inconsistent. Conclusions: Sleep quality is a modifiable and clinically relevant determinant of cardiometabolic health. A multidimensional assessment of sleep-not limited to duration-offers improved risk stratification and highlights potential avenues for preventive interventions.